Application of Airborne LiDAR Measurements to the Topographic Survey of the Tidal Flats of the Northern Jiangsu Radial Sand Ridges in the Southern Yellow Sea - Zhang, Haifeng; Wang, Lian; Zhao, Yifei; Cao, Jicheng; Xu, Min (Frontiers in Marine Science, 2022)
The northern Jiangsu radial sand ridges are typical geomorphic deposit units distributed off the Jiangsu coast. A coastal tidal flat typically develops and provides a good habitat for many migratory birds and benthic organisms. However, topographic surveys of tidal flats have always been difficult in marine surveys because of the dense tidal creek, poor accessibility, and difficulty in setting up control points. In this study, we quickly obtained the point cloud data of the tidal flat near Yangkou Port in the southern part of the radial sand ridges based on an airborne LiDAR system, an integrated 3D laser scanner and a positioning and attitude determination system. We analyzed the adaptabilities of multiple filtering algorithms to tidal flats. In addition, a digital elevation model (DEM) of the tidal flat was constructed and the accuracy was verified with synchronized beach GPS-RTK topographic elevation measurements. The results show that the following: (1) Airborne LiDAR can quickly obtain high precision, high resolution, and a large area of ground point cloud information for tidal flats, overcoming the shortcomings of traditional measurement methods. (2) The triangulated irregular network (TIN) filtering effect is better than that of mathematical morphology and the filtering effect of point cloud normal vector clustering is mediocre. (3) The DEM of the LiDAR point cloud is in good agreement with RTK and the average error of the measurement results is 0.108 m. The error accuracy of the DEM satisfies the surveying specification of a 1:500 topographic map in a flat area, which proves that the airborne LiDAR system can be suitable for tidal flat elevation measurement. Nevertheless, it is possible to provide high precision terrain detection and DEM construction of a tidal flat with the development of airborne infrared and blue-green laser detection radar.